Potential biomarkers and targets in reversibility of pulmonary arterial hypertension secondary to congenital heart disease: an explorative study - Huang, Li (Pulm Circ, 2018)
Whether pulmonary arterial hypertension (PAH) is reversible in congenital heart disease (CHD) is important for the operability of CHD. However, little is known about that. Our research was aimed at exploring novel biomarkers and targets in the reversibility of CHD-PAH. CHD-PAH patients diagnosed with right heart catheterization (RHC) were enrolled (n = 14). Lung biopsy was performed during the repair surgery. After one year follow-up, mean pulmonary arterial pressures (mPAP) were evaluated by RHC to determine the diagnosis of reversible (mPAP < 25 mmHg, n = 10) and irreversible (mPAP ≥ 25 mmHg, n = 4) PAH. Harvested normal lung tissues (n = 6) were included as the control group. Pulmonary arteriole lesions were identified by pathological grading in tissue staining. iTRAQ-labelled mass-spectrometry analysis followed by immunohistochemistry and western blot was used to explore the most meaningful differential proteins. For enrolled patients, the histopathological grading of pulmonary vascular lesions in reversible CHD-PAH patients was all at grades 0–II while grades III–IV were shown only in irreversible CHD-PAH patients. Proteomic analysis identified 85 upregulated and 75 downregulated proteins, including cytoskeletal proteins and collagen chains, mainly involved in cell adhesion, extracellular matrix, cytoskeleton, immune response, and complement pathways. Among them, caveolin-1, filamin A expression, and cathepsin D combined with macrophagocytes counts were significantly increased; glutathione S-transferase mu1 (GSTM1) expression was significantly decreased in the irreversible CHD-PAH group (all P < 0.05). Caveolin-1, filamin A, and cathepsin D expression showed a positive relation and GSTM1 showed a negative relation with pathological grading. Upregulated caveolin-1, filamin A, and cathepsin D combined with increased macrophagocytes and downregulated GSTM1 may be potential biomarkers and targets in the irreversibility CHD-PAH, and which may be useful in evaluating the operability and understanding the irreversibility of CHD-PAH. Expression of these pathological biomarkers combined with pathological changes in lung biopsy may have great value in predicting the irreversibility of PAH.